HUBUNGAN KADAR S100B SERUM TERHADAP LUARAN KLINIS NEUROLOGIS PASIEN STROKE ISKEMIK AKUT - Windri Kartikasari; Retnaningsih Retnaningsih; Amin Husni (PERDOSNI, 2018)
RELATIONSHIP OF S100B SERUM WITH NEUROLOGIC CLINICAL OUTCOME IN ACUTE ISCHEMIC STROKE PATIENTSABSTRACTIntroduction: Biomarker levels of S100B serum have a correlation with the degree of damage to brain tissue so that it can be used as a marker to determine the clinical outcomes of patients with acute ischemic stroke.Aims: To determine the association of S100B serum levels 72 hours of onset to NIHSS score changes in acute ischemic stroke patients. Determine the association of confounding factors that affecting NIHSS score changes and S100B serum levels.Method: This research is an analytic observational study with prospective cohort design. Subjects were patients diagnosed with acute ischemic stroke who meet the inclusion criteria. This study used bivariate and multivariate analysis.Result: There was a significant relationship between S100B serum levels and changes in the NIHSS score. There was a significant relationship between BMI status and NIHSS score changes. There was a significant relationship between S100B serum levels with age ≥65 years, with hypertension, and with dyslipidemia to NIHSS score changes. There was a significant relationship between S100B serum levels in subject ≥65 years old with hypertension to NIHSS score changes. There was no significant relationship between S100B serum levels with dyslipidemia, hypertension, and diabetes mellitus to NIHSS score changes.Discussion: In this study, S100B serum levels were significant correlated with NIHSS score changes in acute ischemic stroke patients. There was a correlation between S100B serum levels with age ≥65 years, hypertension, dyslipidemia. In subjects with age ≥65 years old and hypertension, S100 serum levels was significantly associated with NIHSS score changes in acute ischemic stroke patients.Keywords: Confounding factors, NIHSS score changes, S100B serumABSTRAKPendahuluan: Kadar penanda serum S100B berkorelasi dengan derajat kerusakan jaringan otak sehingga dapat digunakan sebagai petanda untuk mengetahui luaran klinis pasien stroke iskemik akut.Tujuan: Mengetahui hubungan kadar S100B serum 72 jam pasca-onset terhadap perubahan skor NIHSS pada pasien stroke iskemik akut dan faktor-faktor menjadi perancu.Metode: Penelitian ini merupakan penelitian observasional analitik dengan pendekatan kohort prospektif. Subjek adalah pasien yang didiagnosis stroke iskemik akut pertama kali. NIHSS dikatakan membaik jika perubahan skor antara hari ke-7 dan 3 perawatan ≥2. Analisis bivariat dilanjutkan dengan analisis multivariat dilakukan antara NIHSS dengan kadar S100B dan faktor-faktor perancu lainnya.Hasil: Didapatkan hubungan bermakna antara kadar S100B serum dengan perubahan skor NIHSS. Didapatkan hubungan bermakna antara status BMI dengan perubahan skor NIHSS. Terdapat hubungan bermakna antara kadar S100B serum dengan umur ≥65 tahun, dengan hipertensi, dan dengan dislipidemia terhadap perubahan skor NIHSS. Terdapat hubungan bermakna antara kadar S100B serum pada subjek umur ≥65 tahun dengan hipertensi terhadap perubahan skor NIHSS. Tidak terdapat hubungan antara kadar S100B serum dengan dislipidemia, hipertensi, dan DM terhadap perubahan skor NIHSS.Diskusi: Terdapat hubungan antara kadar S100B serum terhadap perubahan skor NIHSS pasien stroke iskemik akut. Terdapat hubungan antara kadar S100B serum dengan dengan umur ≥ 65 tahun, hipertensi, dan dislipidemia. Pada umur ≥65 tahun dengan hipertensi, kadar S100B berhubungan terhadap perubahan skor NIHSS pasien stroke iskemik akut.Kata kunci: Faktor-faktor perancu, perubahan skor NIHSS, S100B serum